The influence of cultural habits on the changing pattern of functional dyspepsia - Yap, Paul; Mahadeva, Sanjiv; Goh, Khean Lee (S. Karger, 2014)
Dyspepsia is a common gastroenterological problem with an estimated global prevalence between 7 and 40%. Functional dyspepsia (FD) is a major economic burden to patients and healthcare systems and significantly affects patient quality of life. The ROME III definition of FD divides it into two subgroups, epigastric pain syndrome and postprandial distress syndrome, the former being more associated with reflux disease and the latter with gastric dysmotility. The global incidence and prevalence of FD continues to rise, but the reason for this is not clear. Rising global obesity and gastroesophageal reflux disease rates may be contributing to the rise in FD. Socioeconomic and cultural demographic changes such as changing dietary habits and rapid urbanization, particularly in the developing countries, are likely to be influencing the course of FD and the way it presents.